Pengaruh Penggunaan Media Sosial Instagram terhadap Sikap Berdonasi Melalui Platform Crowdfunding - Edric Benedict; Angga Ariestya (Universitas Multimedia Nusantara, 2020)
Nowadays, many people donate through the crowdfunding platform. Along with the times, social media has become an effective crowdfunding platform in raising funds. Requests for donations are increasingly made through social media. This study discusses the effect of using Instagram social media from @Kitabisacom on the attitude to donate through the crowdfunding platform using a quantitative-explanative approach. The survey method was carried out by distributing questionnaires to Instagram @Kitabisacom followers (N = 400). The results showed that social media usage significantly influenced the attitude of donating through the crowdfunding platform. Keywords: Social Media, Kitabisa, Attitude, Crowdfunding, Charity Organization